1988
DOI: 10.1161/01.cir.77.2.445
|View full text |Cite
|
Sign up to set email alerts
|

Inducible sustained ventricular tachycardia 4 years after experimental canine myocardial infarction: electrophysiologic and anatomic comparisons with early healed infarcts.

Abstract: We studied a group of 17 dogs 4 to 6 years after infarction produced by 2 hr occlusion of the anterior descending coronary artery followed by reperfusion. Dogs in this "late" infarct group were compared with a group of 24 dogs with "early" healed infarcts (2 to 24 weeks old). With signal-averaging techniques body surface potentials were recorded during sinus rhythm. After thoracotomy epicardial electrograms were recorded from 45 standardized sites within the infarcted region and characteristics of selected ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Results of laboratory (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and clinical (31)(32)(33)(34)(35)(36)(37) studies implicate reentrant mechanisms, at least in part, in the genesis of sustained ventricular tachycardia complicating ischemic heart disease. Abnormal ventricular conduction during sinus rhythm has been observed in regions bordering the infarct (31,32,(38)(39)(40)(41)(42)(43) and appears temporally related to the development of ventricular tachycardia (20)(21)(22)(39)(40)(41)(42)(43).…”
Section: Pathophysiological Basis Of Late Potentialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of laboratory (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and clinical (31)(32)(33)(34)(35)(36)(37) studies implicate reentrant mechanisms, at least in part, in the genesis of sustained ventricular tachycardia complicating ischemic heart disease. Abnormal ventricular conduction during sinus rhythm has been observed in regions bordering the infarct (31,32,(38)(39)(40)(41)(42)(43) and appears temporally related to the development of ventricular tachycardia (20)(21)(22)(39)(40)(41)(42)(43).…”
Section: Pathophysiological Basis Of Late Potentialsmentioning
confidence: 99%
“…Myocardial activation may be delayed because the pathway of excitation is lengthened, conduction velocity is slowed, or both. Structural features may be critical determinants of delayed activation (40,41). Clinically, most myocardial infarcts do not result in complete transmural necrosis (42).…”
Section: Pathophysiological Basis Of Late Potentialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patchy myocardial scars with surviving islands of myocytes characterize human infarcts (10,17). Heterogeneous intramyocardial sympathetic nerve sprouting at scar border zones leads to labile repolarization, increased peak Ca 2ϩ current, and susceptibility to ventricular fibrillation in hypercholesterolemic rabbits (15).…”
mentioning
confidence: 99%
“…(Circulation 1991;84:871-883) P rolongation of electrograms recorded directly from ventricular myocardium can frequently be detected after experimental and clinical myocardial infarctions.1-10 Prolonged, fractionated electrograms are thought to be generated by slow and inhomogeneous activation of adjacent muscle fibers, resulting from impairment of cell-to-cell coupling by graphic potentials at the end of the QRS complex that are not detectable by standard electrocardiography (ECG).12-16 These electrocardiographic "late potentials" are commonly seen in patients with sustained ventricular tachycardia16-18; in canine infarct models, they are associated with inducible ventricular arrhythmias. [19][20][21][22] Late potentials are thought to arise from tissue that generates prolonged, fractionated electrograms. Studies in humans and canine infarct models have shown an association between the presence of late potentials and the presence of prolonged electrograms.121519,2123,24 For example, Spear et al19 showed in a canine infarct model that dogs with inducible ventricular tachycardia generally had both electrocardiographic QRS late potentials and prolonged ventricular epicardial electrograms and that dogs without inducible arrhythmias generally had neither.…”
mentioning
confidence: 99%